The effect of educational support intervention including peer groups for infant care on the growth rates of infants, breastfeeding self-efficacy and quality of life of their mothers in Iran: study protocol - Forogh Okhovat; Shirin Okhovat; Zohreh Karimiankakolaki; Nooshin Yoshani (BMC, 2022)
Plain language summary Mothers' knowledge about the infant's problems and provide the necessary care can increase the mother's confidence in providing care for her infant and eliminate misconceptions in primiparous mothers. This quasi-experimental study is an educational support intervention protocol for infant care that will be conducted in two phases. The educational support program will be designed in the first phase. The program includes educational sessions on breastfeeding, growth and development of infants and cares for children under one year of age in a virtual group where a physician, a nurse, a midwife and a healthcare provider are also present. Using the opinions of the experts, the peer group will discuss various points and the research team will finalize the program based on priorities. The second phase of the educational intervention will be conducted experimentally as a pretest-posttest design for the intervention and control groups. The present study will be conducted to evaluate the effect of educational support intervention including peer groups for infant care on the growth rates of infants, breastfeeding self-efficacy and quality of life of their mothers in Iran.